Dental implants placed in previously failed sites: survival rate and factors affecting the outcome - Machtei, Eli E.; Mahler, Dan; Oettinger-Barak, Orit; Zuabi, Otman; Horwitz, Jacob (Clinical oral implants research, 2008)
Objectives: The purpose of the present study was to evaluate the survival rate of dental implants in previously failed implant sites. In addition, factors that might affect the outcome of these redo procedures were also explored. Material and methods: Patients that had failed dental implants, which were replaced with the same implant type at the same site, were included. Data on the failed implants were collected. The same parameters, along with the interval between retrieval and re‐implantation, were collected for the second set of implants. Descriptive statistics were used to describe the patients and implants. Life table analysis of these implants was tabulated for both implant sets. The effect of systemic, environmental and local factors on the survival of the redo dental implants was evaluated. Results: Fifty‐six patients with a total of 79 redo implants were included in this study. Implants were followed for 7–78 months (mean 29.9±2). Thirteen implants failed that resulted in an overall survival rate of 83.5%. Successful implants had greater diameter (4.05±0.52 mm) than failed implants (3.72±0.56 mm); however, these differences were only marginal (P=0.06). Conversely, smoking habits, implants length and location, mode of placement and spontaneous exposure did not have a significant effect on the outcome of this procedure. Conclusion: Redo of dental implants has a lesser survival rate compared with previous reports for implants in pristine sites. These results were not associated with most implant‐ and/or patient‐related factors. Thus, a possible negative effect that is associated with the specific implant's site might account for this phenomenon.